The Effects Of Transcutaneous Electrical Nerve Stimulation Applied in the Early Postpartum Period After Cesarean Birth on Healing, Pain, and Comfort - Baransel, Esra Sabanci; Barut, Suemeyye; Ucar, Tuba (Wiley, 2024)
Introduction: This study was conducted to determine the effects of transcutaneous electrical nerve stimulation (TENS) applied in the early postpartum period after cesarean birth on incision site healing, postoperative recovery, pain, and comfort. Methods: This randomized, single-blind, placebo-controlled study was conducted with 138 women (TENS group n = 46, placebo group n = 46, control group n = 46) who gave birth by cesarean between January and September 2023. TENS was applied twice at a frequency of 100 Hz with a pulse width of 100 microseconds, at 10 to 12 and 14 to 16 hours after birth, for 30 minutes each. Outcomes were measured with the Postoperative Recovery Index; Redness, Edema, Ecchymosis, Discharge, and Approximation Scale; Visual Analogue Scale; and Postpartum Comfort Questionnaire. Outcomes between groups were compared postintervention, correcting for baseline using analysis of covariance. The study was registered at (NCT05991921). Results: Mean scores for postoperative recovery were significantly lower (improved) in the TENS group (113.58) compared with the placebo and control groups (134.67, 136.61; P < .001). The postoperative recovery subscales (psychological symptoms, physical activities, appetite symptoms, bowel symptoms, general symptoms) were also significantly decreased in the TENS group compared with the placebo and control groups. Similarly, mean scores for postpartum comfort, and the corresponding physical comfort, psychospiritual comfort, and sociocultural comfort subscales, were significantly improved in the TENS group (110.26) compared with the placebo and control group (83.80, 81.19; P < .05). Discussion: TENS application can be preferred as an alternative method to increase pain control, recovery, and patient comfort after cesarean birth.
Keywords: TENS; cesarean birth; incision site healing; postoperative recovery; pain; comfort; postpartum